A drop in the bucket: examining practice and policy for water resilient urban agriculture and urban food system resilience - Chhour, Kristida; Carrasquillo, Maya (Frontiers in Sustainable Food Systems, 2025)
Climate change is increasing the frequency and intensity of disasters that disrupt supply chains and threaten urban food supplies. Urban agriculture can make urban food systems resilient to such threats by localizing food production and recycling urban waste as food production inputs. The urban environment, however, brings unique water access and management challenges that can threaten the viability of urban agriculture, particularly in water-scarce regions. This case study of the San Francisco East Bay, a region vulnerable to water scarcity, examines (1) how stakeholders manage water resources for urban agriculture under water-scarce conditions and (2) the potential for urban agriculture to be both water resilient and a contributor to overall urban resilience. We employed a mixed-methods approach consisting of identifying and mapping 91 urban agriculture sites, interviewing 34 stakeholders, and analyzing the region's general and climate action plans. Urban growers were the main actors in water management, and they maximized water conservation regardless of drought conditions. Municipalities and water utilities were minimally involved in water management for urban agriculture, but provided access to land and water. Land access played a significant role in water access by dictating the available infrastructure and water pricing. We found a large gap between the actual practice of urban agriculture and the idealized systems modeled in academic literature. Although urban agriculture sites withstood previous droughts, they had not implemented water resilience strategies, such as urban greywater and reclaimed water use, that are often modeled in studies on urban agriculture and resilience. Sites were dependent on municipal water sources. Institutional support is necessary to stabilize long-term access to land and water at urban agriculture sites. With greater stability, urban agriculture can further pursue infrastructural improvements that enhance water resilience and overall food system resilience.